Experimental and analytical characterization of steel shear links for seismic energy dissipation. (1st October 2018) - Nuzzo, Iolanda; Losanno, Daniele; Caterino, Nicola; Serino, Giorgio; Bozzo Rotondo, Luis M.
Highlights: A new SL damper is experimentally investigated, analyzing its competitiveness due to changeable mechanical properties with geometry. SL device has already been applied for new constructions and retrofit of existing buildings in South America. A fully bolted connection is proposed to make easier installation without welding. A properly designed set up system is proposed for monotonic and cyclic application of force up to 1000 kN. Simple analytical formula are proposed to estimate mechanical properties. Abstract: This paper describes the experimental investigation on a newly designed steel shear link (SL) for seismic protection of civil structures. It is a low-cost hysteretic device, realized from a single steel plate where variable thickness is given through milling. It has been already adopted for several applications in South America, both for new constructions and seismic retrofit of existing buildings. Even small variation of device's geometry can significantly modify its mechanical behavior, both in terms of strength and stiffness, making such devices very appealing for the flexibility in terms of design solutions. SL device is conceived to be connected to the main frame through bolted connections and mounted on a supporting brace. In particular, slotted holes on one edge of the damper prevent the device from transmitting shear to the upper beam during the seismic excitation. A couple of specimens for each of 5 different geometries has been tested, for a total of 10 tests. Two different boundary configurations have been considered, analyzing results of fully-tightened or not fully-tightened bolts in correspondence of slotted holes. The set-up system has been properly designed to apply forces up to 1000 kN, to be able to accommodate and test the largest specimens of the set. The paper presents the experimental results and data processing concerning analysis of deformation process, hardening behavior and collapse. The main features of the control devices are highlighted, above all, the high dissipative capability that is mainly due to the particular shape of the steel damper, which leads to a high buckling resistance.